2023
DOI: 10.1021/acs.nanolett.3c03341
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Multiscale Mechanical Indexes for Assessing Liver Fibrosis and Treatment Outcomes

Zhuo Chang,
Liqiang Zhang,
Jiu-Tao Hang
et al.

Abstract: Understanding liver tissue mechanics, particularly in the context of liver pathologies like fibrosis, cirrhosis, and carcinoma, holds pivotal significance for assessing disease severity and prognosis. Although the static mechanical properties of livers have been gradually studied, the intricacies of their dynamic mechanics remain enigmatic. Here, we characterize the dynamic creep responses of healthy, fibrotic, and mesenchymal stem cells (MSCs)-treated fibrotic lives. Strikingly, we unearth a ubiquitous two-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This difficulty can lead to an incorrect calculation of the overall sample deformation during the creep response, resulting in invalid theoretical calculations; (2) the creep response can be significantly influenced by the localized tissue microstructure, which exhibits notable variability at the microscale. Our previous histological analysis (Chang et al 2023b) revealed a noticeable heterogeneity in tissue components. The presence of excessive porous tissue microstructure can further contribute to an unstable creep response during force clamping, leading to difficulties in theoretical analyses.…”
Section: Missing Value Imputationmentioning
confidence: 92%
See 2 more Smart Citations
“…This difficulty can lead to an incorrect calculation of the overall sample deformation during the creep response, resulting in invalid theoretical calculations; (2) the creep response can be significantly influenced by the localized tissue microstructure, which exhibits notable variability at the microscale. Our previous histological analysis (Chang et al 2023b) revealed a noticeable heterogeneity in tissue components. The presence of excessive porous tissue microstructure can further contribute to an unstable creep response during force clamping, leading to difficulties in theoretical analyses.…”
Section: Missing Value Imputationmentioning
confidence: 92%
“…The research process was built upon the dataset initially compiled and analyzed in our prior research (Chang et al 2023b). In our previous study, we extensively characterized the dynamic creep responses and multiscale viscoelastic properties of healthy, fibrotic, and treated liver tissues, employing AFM-microrheology and self-similar hierarchical theory (figure 1(A)).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a large volume of AFM studies reported that individual cancer cells are less rigid than their normal counterparts [3] , [9] , [10] , [11] , [12] , and the same trend was also observed comparing normal and cancerous tissues of the human breast [13] . Beyond cancer, other diseases like osteoarthritis [14] , [15] , tissue fibrosis [16] , [17] and myocardial infarction [18] exhibit distinguished mechanical signatures, which can be used as an advantageous technique to develop early diagnosis methods. More recently, a few works reported the strong role the microenvironment topography plays in cell mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Collective cell migration is essential for many physiological and pathological processes, including embryogenesis, tissue development, wound healing, and cancer metastasis. Much effort has been devoted to comprehensively exploring the intricate physical mechanisms that underlie collective motion behaviors. Recent experiments have uncovered a striking emergent phenomenon, wherein a mechanical wave spontaneously arises and propagates within collective cells, which was widely observed in confined clusters, expanding colonies and colliding monolayers . Especially, Madin–Darby Canine Kidney (MDCK) epithelial cells exhibit an X-pattern mechanical wave during their expansion toward free regions .…”
mentioning
confidence: 99%